Sustainable Agriculture: Empowering Youth Organization through The Modernization of Forage Technology in Desa Ganjarsari - Sukmayadi, Qolbi Mujahidillah Adzimat; Asyahidda, Fajar Nugraha (Universitas Dinamika, 2024)
RW 03 Desa Ganjarsari, Kecamatan Cikalong Wetan, Kabupaten Bandung Barat, Jawa Barat is an area that has a lot of potential for goat farming, particularly for youths who are involved in youth organizations and who also own agriculture businesses. Thus, the preparation and accessibility of conventional animal forage are the matter at hand. This empowerment program's purpose is to provide training in the production of complete fermented silage forage as a modern forage technology to promote sustainable agriculture among youths. The program is put into action using the discussion technique for planning, the learning-by-doing method for executing it out, both verbal and written evaluation methods, as well as the testing of products to determine the program's effectiveness. The outcomes include guidelines for making complete fermented silage, increased awareness of the youth organization, their ability to produce modern forage, and their willingness to act as change agents to modernize forage technology in order to achieve sustainable agriculture in the area as a whole. It has been proven as an improvement towards modern farm activities, since one of the parameters of modern farm activity is the ability to overcome low forage quality. Further development needs to be made, including the establishment of youth-based farm groups and discussions on the well-being of goats and stables.